2013
DOI: 10.1007/s13197-013-1035-6
|View full text |Cite
|
Sign up to set email alerts
|

Shellac and Aloe vera gel based surface coating for shelf life extension of tomatoes

Abstract: Shellac (S) and Aloe vera gel (AG) were used to develop edible surface coatings for shelf-life extension of tomato fruits. The coating was prepared by dissolving dewaxed and bleached shellac in an alkaline aqueous medium as such as well as in combination with AG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 12 publications
3
43
0
2
Order By: Relevance
“…Alterations in the fruit physiological activities seriously affected the fruit texture in postharvest studies of the commodities. Coating material retained the texture of fruit due the slowdown biochemical and ripening agent's activities [42]. Similar observations were also taken by [6, 14, 17] in sweet cherry, peach and in plum and suggested that coating material of Aloe Vera gel had antimicrobial properties which reduced decay loss and microbial attack and retained the fruit texture.…”
Section: Organoleptic Evaluationsupporting
confidence: 78%
“…Alterations in the fruit physiological activities seriously affected the fruit texture in postharvest studies of the commodities. Coating material retained the texture of fruit due the slowdown biochemical and ripening agent's activities [42]. Similar observations were also taken by [6, 14, 17] in sweet cherry, peach and in plum and suggested that coating material of Aloe Vera gel had antimicrobial properties which reduced decay loss and microbial attack and retained the fruit texture.…”
Section: Organoleptic Evaluationsupporting
confidence: 78%
“…In their former work, Maftoonazad and Ramaswamy (2005) reported that firmness value in coated samples was almost 1.5 times higher than that of uncoated fruits, as reported for avocados coated with methylcellulose. Similarly, Chauhan et al (2013) indicated that Shellac based surface coating retained tomatoes" firmness better than control fruits. Delay in loss of cell wall firmness might be associated with limited availability of oxygen from the ambient atmosphere for respiration process and subsequent delay on cell wall degradation.…”
Section: Fruit Firmnessmentioning
confidence: 94%
“…Throughout the storage period, the firmness had been retained significantly (p ≤ 0.05) higher in coated samples compared to the uncoated fruits during storage, the retention being maximum (3.3 kg) in the case of zein + cystein-coated jamun fruits. The retention of the firmness could be attributed to the restriction in metabolic activities associated with cell wall-degrading enzymes (Chauhan et al 2013). According to Salunkhe et al (1991), low levels of O2 and high levels of CO2 limit the activities of these enzymes and allow retention of the firmness during storage.…”
Section: Effect On Firmness and Softening Related Enzymesmentioning
confidence: 99%